Model Bermain Sambil Belajar Sains untuk Mengembangkan Keterampilan Proses Peserta Didik di Tk Dharmawanita UNP Padang - Indra Yenni (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2012)
This research constitutes the application of learning throught game model while learning science with the topic of floating and drowning objects in an effort to develop the process skills of the learners in kindergarten. The purpose of this study is to determine whether the model of playing game while learning applied in learning sciences can develop process skills of kindergarten students, which include observing, classifying, and communicating the results of the experiment. This classroom action research consisted of two cycles and each cycle consisted of planning, implementation, observation, and reflection stages. The data were obtained through documentation, observation, and tests. The data were analyzed by using the percentage of learning mastery. The result of research shows that the model of playing game while learning science can improve the process skills of the learners. Then other researchers are suggested to conduct further research with varied learning scenarios and evaluation systems. Key words: playing game, learning science, kindergarten, learning throught game